2007
DOI: 10.1002/cncr.22476
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities of epidermal growth factor receptor in lung squamous‐cell carcinomas, adenosquamous carcinomas, and large‐cell carcinomas

Abstract: We tested the hypothesis that C57BL/6J mice will model human metabolic interactions between dl‐methylphenidate (MPH) and ethanol, placing an emphasis on the MPH transdermal system (MTS). Specifically, we asked: (1) will ethanol increase d‐MPH biological concentrations, (2) will MTS facilitate the systemic bioavailability of l‐MPH, and (3) will l‐MPH enantioselectively interact with ethanol to yield l‐ethylphenidate (l‐EPH)? Mice were dosed with MTS (¼ of a 12.5 cm2 patch on shaved skin) or a comparable oral dl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 41 publications
3
45
0
Order By: Relevance
“…All patients bearing a EGFRvIII mutation were male, smokers, and seven had squamous cell carcinoma, whereas one had poorly differentiated adenocarcinoma. However, in the investigation of Ohtsuka et al, 99 EGFRvIII mutation was detected in one of seven squamous cell carcinomas with an adenocarcinoma component, in two of four adenosquamous carcinomas and in one of seven large cell carcinomas.…”
Section: Egfrviii Mutationmentioning
confidence: 89%
See 3 more Smart Citations
“…All patients bearing a EGFRvIII mutation were male, smokers, and seven had squamous cell carcinoma, whereas one had poorly differentiated adenocarcinoma. However, in the investigation of Ohtsuka et al, 99 EGFRvIII mutation was detected in one of seven squamous cell carcinomas with an adenocarcinoma component, in two of four adenosquamous carcinomas and in one of seven large cell carcinomas.…”
Section: Egfrviii Mutationmentioning
confidence: 89%
“…The information concerning whether EGFRvIII mutation is associated with specific histological types of lung cancer is conflicting, although most studies have indicated that EGFRvIII is associated with squamous cell carcinoma. 98,99 In the study by Sasaki et al, 97 EGFRvIII mutation was detected in 3% (8/ 252) of non-selected lung cancer patients. All patients bearing a EGFRvIII mutation were male, smokers, and seven had squamous cell carcinoma, whereas one had poorly differentiated adenocarcinoma.…”
Section: Egfrviii Mutationmentioning
confidence: 98%
See 2 more Smart Citations
“…Activating mutations in this receptor tyrosine kinase cause constitutive activation of the mitogen-activated protein kinase pathway, driving increased cellular motility, invasiveness, and resistance to apoptosis. Activating EGFR mutations are known to underlie a significant number of adenocarcinomas 4 , but can also be the drivers behind a smaller number of adenosquamous 5 or squamous cell carcinomas harbouring adenocarcinomatous components 6 . Established clinical risk factors for an egfr-driven lung cancer include female sex and absence of a heavy tobacco-smoking history 7 .…”
Section: Introductionmentioning
confidence: 99%